Correlation of Epstein-Barr virus copy numbers, MICA expression and rs2596542 variant in nasopharyngeal carcinoma tumour - Thanh Dat Ta; Khanh Tran Van; Thanh Binh Nguyen; Manh Thuong Le; Long Ha Le Hai; Hoang Viet Nguyen (Vietnam Journal of Science, Technology and Engineering, 2023)
Major histocompatibility complex class I chain-related A (MICA) is a tumour antigen that is greatly expressed on the surfaces of human malignancies and infection cells, which trigger attachment to immune cells. Although many studies have investigated the role of the MICA rs2596542 variant involved in high risk of hepatocellular carcinoma (HCC), the expression regulation of rs2596542 MICA in nasopharyngeal carcinoma (NPC) susceptibility with the Epstein-Barr virus (EBV) is still ambiguous. Therefore, this study was conducted to elucidate the association of rs2596542C/T and EBV load to MICA expression in NPC tissues. A total of 70 tumour tissues from NPC patients were enrolled in the current study . The genetic variant of rs2596542 was identified by Real-time PCR genotyping, and MICA protein expression was quantified by immunohistochemistry staining. A significant difference was observed in the expression of MICA regarding EBV copy numbers (p<0.01). High expression of MICA presented a considerably lower EBV status. In addition, higher expression of homologous MICA rs2596542 CC was significantly associated with a lower EBV load (p<0.001) thus suggesting a protective role of allele C against the infection of EBV. In summary , rs2596542 MICA plays an important role in the immune response preventing the EBV among NPC patients as well as developing a new predictive biomarker for virus susceptibility to cancers.